Globalization and national financial systems - Hanson James A; Honohan Patrick; Majnoni Giovanni (Washington World Book, 2003)
This book breaks new ground by exploring the challenges, constraints, and opportunities of national financial systems in developing countries, while noting that all such systems must be considered small when viewed in the context of global finance. Banki
Keywords: Banks and banking; Finance; Globalization-economic aspects; International finance; Monetary policy